Innovative comics – cacaniweb application - Tan, Gwendalena Hui Ling. (2010)
Drawing comics has become increasingly popular in today’s context where people need not be an artist to draw comics. With advanced technology today, drawing is made easier and accessible with web technology. Users can now go onto the Internet and use drawing web applications to draw. Web applications are common and almost everyone in the world is using the Web. Web applications must be user-friendly so that non IT-savvy can also use the application. Therefore, this leads to the idea of creating a web-based comic drawing tool which is free for user.